METODOLOGI TAFSIR EKOLOGI: (Studi Komparasi Pemikiran Quraish Shihab dan Abdul Mustaqim) - Siti Mahmudah (Lembaga Sepercenter, 2026)
This research is motivated by the growing severity of the global ecological crisis, which has not only drawn the attention of scientists and policymakers but has also encouraged the emergence of new awareness among Muslim thinkers. The Qur’an, as the holy scripture of Islam, contains fundamental principles related to environmental preservation, making it relevant to be studied through the perspective of ecological exegesis. In this context, Quraish Shihab and Abdul Mustaqim are two important figures who both pay great attention to environmental issues, albeit with different methodologies and exegetical approaches. This study employs a qualitative method with a library research approach. The analysis technique used is comparative analysis, examining the thought of Quraish Shihab in his book Islam & Lingkungan (Islam and the Environment) and Abdul Mustaqim in his book Tafsir Ekologi: Relasi Eko-Teologis Tuhan, Manusia, dan Alam (Ecological Exegesis: The Eco-Theological Relationship of God, Humans, and Nature). The findings show that both figures share similarities in making the Qur’an the primary foundation, integrating reason, classical exegesis, and modern science in interpretation, and emphasizing moral values in preserving nature. However, there are methodological differences: Quraish Shihab emphasizes a normative-moral approach with a reflective and contextual exegetical style, viewing the environmental crisis as part of a broader spiritual and moral crisis of humanity. Meanwhile, Abdul Mustaqim highlights an eco-theological approach with a critical-emancipatory style, emphasizing the triadic relationship between God, humans, and nature, with a stronger orientation toward social transformation. Thus, this research affirms that the ecological exegesis methodologies developed by Quraish Shihab and Abdul Mustaqim complement one another. Both contribute significantly to the development of contemporary ecological exegesis, which is not only normative but also applicative in providing real solutions to global environmental problems.